Human behaviour in emergency situations: comparisons between aviation and rail domains - Stedmon, Alex; Lawson, Glyn; Lewis, Laura; Richards, Dale; Grant, Rebecca (Palgrave Macmillan, 2015)
This article presents a comparative review of the knowledge base regarding human behaviour in emergencies for both aviation and rail domains. Generic models of human behaviour in emergency situations are introduced and specific attention is then focussed on methods of behaviour prediction, exhibited behaviours in emergencies and methods of aiding evacuation across both modes of transport. Using established knowledge from the aviation domain, it has been possible to make observations and comparisons about the rail domain. Traditionally, the aviation domain has been a major focus of research attention and this is used to inform and interpret the rail domain. By drawing comparisons across these domains for human behaviour in emergency situations, the observations are discussed along with recommendations for future policies/planning for emergencies and future research areas.